Desarrollo de una metodología para mejorar la productividad del proceso de elaboración de tubos plásticos - Jurado Mayorga, Jorge L. (2010)
The current project looks for the enhancement of the productivity of a line of production that elaborates plastic pipes. Waste in the line of production that causes low development in the process will be eliminated through the application of methods based in the lean manufacturing. The main aim is to apply a methodology based in the principles and techniques of the lean manufacturing in order to improve the productivity in the process of plastic pipes manufacturing. To accomplish this aim, the problems presented in the manufacturing process were identified through an interview to the manager of the factory, selecting and prioritizing the problems to be eliminated or minimized. The people involved with the operations in the line of production were interviewed in order to obtain information about the waste found in the operations. The waste that represented a bigger negative impact for the performance of the line was analyzed and prioritized in order to eliminate it.